Challenges of developing a takāful retirement annuity plan in Malaysia - Younes Soualhi (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to explore the challenges facing the development of a takāful retirement annuity plan in Malaysia. It also aims at exploring a new platform to re-launch the same product after being withdrawn from the Malaysian annuity market a few years ago. Design/methodology/approach: The research adopts a qualitative approach to address the possible challenges hindering the development of a takāful retirement annuity plan in Malaysia. The research will not discuss the Sharīʿah issues deemed settled in previous researches but will only focus on technical challenges related to the instruments of investment and prudential measures. Findings: The research found that various challenges face the development of a takāful annuity plan in Malaysia. Some of those challenges are the downsizing of the ṣukūk market, the shortage of long-term ṣukūk, longevity risk and risk-based capitalization. The research found that there is a need for a diversified portfolio of securities instead of solely using ṣukūk as an investment instrument in this product. Originality/value: Re-launching the takāful annuity plan in Malaysia requires the identification of actual challenges facing the development of such a product. The product purported to be re-launched would benefit a large segment of retirees who do not have enough savings during the retirement age. The introduction of such a product will also expand the takāful market in annuities, which remains untapped.
Keywords: 330; Takāful; Retirement annuity plan; Longevity risk; Ṣukūk